2010
DOI: 10.1007/s11431-010-0032-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, viscosity and thermal conductivity of CaCO3 aqueous nanofluids

Abstract: CaCO 3 aqueous nanofluids were prepared by dispensing aqueous CaCO 3 paste into distilled water under ultrasonic vibration. The actual microstructures of the CaCO 3 nanofluids with different particle volume fractions were characterized by freeze etching replication transmission electron microscopy (FERTEM). Thermal conductivity and rheological behavior of the nanofluids were measured by standard analyzers. The results show that CaCO 3 paste as raw material for nanofluids is advantageous to reducing aggregation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(17 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…The precipitate trapped between the calcite surfaces was likely denser and more viscous than the bulk solution. Although the exact viscosity of the precipitate was unknown (and the effective viscosity of the confined solution was influenced by the inhomogeneous distribution of the clustered precipitate in the gap), high viscosity has been previously observed in colloidal suspensions of CaCO 3 nanoparticles 74 . Due to viscous forces, the precipitate would oppose the movement of the surfaces (similarly to what has been previously observed in SFA force measurements with non-adsorbing polymer melts 73 ), giving rise to repulsive force on approach and hystereses between loading-unloading force curves.…”
Section: Resultsmentioning
confidence: 99%
“…The precipitate trapped between the calcite surfaces was likely denser and more viscous than the bulk solution. Although the exact viscosity of the precipitate was unknown (and the effective viscosity of the confined solution was influenced by the inhomogeneous distribution of the clustered precipitate in the gap), high viscosity has been previously observed in colloidal suspensions of CaCO 3 nanoparticles 74 . Due to viscous forces, the precipitate would oppose the movement of the surfaces (similarly to what has been previously observed in SFA force measurements with non-adsorbing polymer melts 73 ), giving rise to repulsive force on approach and hystereses between loading-unloading force curves.…”
Section: Resultsmentioning
confidence: 99%
“…This enhancement is in agreement with other reports in the literature for thermal conductivity of the graphene composites [ 53 ]. While, the thermal diffusivity of graphene nanofluid is not available in the literature, some good amount works have been carried out in the literatures to investigate thermal conductivity of graphene solutions in a variety of solvents [ 46 , 54 58 ]. Accordingly, the thermal conductivity of the suspension is represented by K n = α n ( ρ n C n ) Where α n , ρ n and C n are the thermal diffusivity, density and specific heat capacity of the nanofluids.…”
Section: Resultsmentioning
confidence: 99%
“…It suggested that CaCO 3 nanoparticles were spherical shape, while micro‐CaCO 3 was square and massive, and their particle sizes were several orders of magnitude difference, which was consistent with the particle size measured in Table 1. Micron CaCO 3 slurry and CaCO 3 nanofluids were fabricated by two‐step method 31 . In this section, sodium dodecylsulphate (SDS) was mixed into the suspensions as a dispersant to prevent the aggregation of particles, then the mixture was stirred and mixed by a magnetic stirrer, finally an ultra‐sonication homogenizer Sonifier 250 (Branson Ultrasonics, Danbury, USA) was utilized about 3 hours to make the mixture more uniform.…”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…Micron CaCO 3 slurry and CaCO 3 nanofluids were fabricated by two-step method. 31 In this section, sodium dodecylsulphate (SDS) was mixed into the suspensions as a dispersant to prevent the aggregation of particles, then the mixture was stirred and mixed by a magnetic stirrer, finally an ultra-sonication homogenizer Sonifier 250 (Branson Ultrasonics, Danbury, USA) was utilized about 3 hours to make the mixture more uniform. The prepared micron CaCO 3 slurry and two types of CaCO 3 nanofluids were of the same concentration, which were from 1 to 7 vol % respectively, as determined by Equation (1).…”
Section: Materials and Preparationmentioning
confidence: 99%